Strategies in Improving Sensitivity of Colorimetry Sensor Based on Silver Nanoparticles in Chemical and Biological Samples - Hanim Istatik Badi'ah; Dinda Khoirul Ummah; Ni Nyoman Tri Puspaningsih; Ganden Supriyanto (Indonesian Journal of Chemistry, 2022)
Colorimetric sensors-based silver nanoparticles (AgNPs) are very interesting to be studied and developed because of the simplicity and ease in the principle of detection. It does not require sophisticated and affordable tools but still has high sensitivity. The coefficient extinction of AgNPs is relatively higher than AuNPs of the same size, making the sensitivity of AgNPs higher than AuNPs. The principle of detection is based on the aggregation of nanoparticles with analytes that causes shifting in Localized Surface Plasmon Resonance (LSPR) to a larger wavelength, commonly called a bathochromic shift or redshift. It is a favorite phenomenon because it is more easily observed with naked eyes. This sensor shows a good analytic performance with high sensitivity due to strong LSPR and good strategies that selectively bring interaction between analytes and AgNPs. AgNPs are characterized using UV-Visible (Ultra Violet-Visible), TEM (Transmission Electron Microscope), FTIR (Fourier Transform Infrared), and DLS (Dynamic Light Scattering), and many analytes have been detected with this sensor successfully. This article discusses several important parameters in increasing the sensitivity of AgNPs colorimetric sensors. Finally, it can be used as guidelines in the development of methods in the future.